The Use of Think, Pair, Share Learning Method to Improve Vocabulary Mastery of the Second Class Students of Muhammadiyah Vocational High School, Salatiga in Academic Year 2011/2012 - Hidayati, Ida Ubaidah (Vision: Journal for Language and Foreign Language Learning, 2017)
The Aim of this research is to what extent does "Think, Pair, Share" use to improve the students' interest in the teaching-learning process for second class students of SMK Muhammadiyah Salatiga. The methodology of the study is classroom action research, where the writer as a teacher in the teaching-learning process, and writer had a partner as observer in learning activities. The objectives of the study are to what extent does "Think, Pair, Share" use to improve the vocabulary mastery, and to what extent does "Think, Pair, Share" use to improve the vocabulary mastery for the second year students of SMK Muhammadiyah Salatiga. The writer applied test, namely pre-test, and post-test. She implemented three cycles. Each consists of planning, implementation of the action, observation, and reflection. The finding shows that Think, Pair, Share learning method can improve vocabulary in teaching-learning process. It can be seen by the result of pretest and posttest in cycle I is 5.49, cycle II is 6.32, and cycle III is 8.03. From the result is greater than t-table with n=33 is 0.42. It means that the use of TPS can improve the student's vocabulary mastery.